Corporate Governance in Libyan Public Listed Companies - Omar, Khairi Mohamed (2010)
The purpose of this study is to look into the relationship between corporate governance and firm financial performance in Libyan public listed companies. All the data was collected using questionnaires and also secondary data gathered through use of annual reports for public listed companies in Libya from the Central Bank of Libya. A total of 250 questionnaires were distributes to most of the public listed companies. The correlation analysis was looked into for determining the relationship of different variables that were used in this study which are ownership, responsibility of board and management, shareholders and stakeholders, and disclosure and auditing. Even though the questionnaires that were submitted were only 144 it was concluded that there is no significant relationship between corporate governance and firm financial performance considering the variables used. The lack of adequate time to complete a full analysis of the findings and data gathered may also have contributed to the results of this study. Also getting the questionnaires back from different respondent was hard although enough questions were made available to carry out the study. Since the study focuses on use of Likert scale, correlation analysis, and regression analysis used to determine the significant of the variables used, the major contribution of this study was to compare if there is relationship between corporate governance and firm financial performance in Libyan public listed companies. This will help to determine the influence of corporate governance in public listed companies operating in Libya. This study looked at the corporate governance and firm financial performance for public listed companies in Libya.